Ethical Leadership: Literature Study - Maslahatun Kamilah; Urjuan Mamduh; Ira Alvina Damayanti; Mochammad Isa Anshori (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the role of ethical leadership in bilding a healthy and sustainable company. This study also aims to explore the perspectives of Heifetz and Burns regarding ethical leadership, explore the dark side of ethical leadership, and analyze the principles of ethical leadership. The library method approach or literature study was used in this study, by utilizing various sources of literature to obtain data. The qualitative approach was chosem because the data produced is in the form of descriptions or words. The results of this study indicste that ethical leadership plays a very important role in the success of an organization. Strong leadership ethics can help organizations increase trust, motivate employees, reduce the risk of violations of law and ethics, increase competitiveness, and strengthen organizational culture. The dark side of leadership ethics, such as the abuse of power, must be avoided so as not to damage the image of the organization. Ethical leadership principles, such as integrity, honesty, and responsibility, are also very important for a leader who has good ethics can bring the company to the peak of success by exploiting the potential possessed by employee